Breaking linear scaling relationships in oxygen evolution via dynamic structural regulation of active sites - Zheye Zhang; Hongyan Zhao; Shibo Xi; Xiaoxu Zhao; Xiao Chi; Hong Bin Yang; Zhongxin Chen; Xiaojiang Yu; Yang-Gang Wang; Bin Liu; Peng Chen (Nature Communications)
Abstract The universal linear scaling relationships between the adsorption energies of reactive intermediates limit the performance of catalysts in multi-step catalytic reactions. Here, we show how these scaling relationships can be circumvented in electrochemical oxygen evolution reaction by dynamic structural regulation of active sites. We construct a model Ni-Fe2 molecular catalyst via in situ electrochemical activation, which is able to deliver a notable intrinsic oxygen evolution reaction activity. Theoretical calculations and electrokinetic studies reveal that the dynamic evolution of Ni-adsorbate coordination driven by intramolecular proton transfer can effectively alter the electronic structure of the adjacent Fe active centre during the catalytic cycle. This dynamic dual-site cooperation simultaneously lowers the free energy change associated with O–H bond cleavage and O–O bond formation, thereby disrupting the inherent scaling relationship in oxygen evolution reaction. The present study not only advances the development of molecular water oxidation catalysts, but also provides an unconventional paradigm for breaking the linear scaling relationships in multi-intermediates involved catalysis.